A Novel Canine Mammary Cancer Cell Line: Preliminary Identification and Utilization for Drug Screening Studies - Li, Rifei; Wu, Haoxian; Sun, Yue; Zhu, Jingru; Tang, Jun; Kuang, Yu; Li, Gebin (Frontiers in Veterinary Science, 2021)
Canine malignant mammary tumor is a dangerously fatal cancer disease with poor survival in female dogs. The aim of this study was to preliminary characterize a novel canine mammary cancer cell line, B-CMT, from canine primary mammary gland tumor, and utilize it as a cell model to screen for possible therapeutic drugs in vitro. The successfully established cell line, B-CMT, for culturing over 50 passages. B-CMT has a fast proliferation rate, and the population doubling time (PDT) of B-CMT cells was calculated to be 33.6 h. The B-CMT cell line lacked human epidermal growth factor receptor-2 (HER-2), estrogen receptors (ER) and progesterone receptors (PR) expression by qRT-PCR. Compared with MDCK cells, CMT cell lines CDH1 expression significantly decreased or even disappeared, as well as TGF-β expression didn’t change on B-CMT. Interestingly, the B-CMT cell line from canine primary tumor also showed a positive to hypoxia inducible factor-1α (HIF-1α) immunofluorescence (IF) and western blot analysis. The Transplanted tumor mouse formed a palpable soft tissue mass after 10 days of inoculation with EGFP-B-CMT (B-CMT cells stably expressing EGFP), which histologically resembled the canine primary tumor, and was derived from B-CMT cell line through detecting EGFP by immunohistochemical (IHC) analysis. Moreover, we investigated the cytotoxicity of five drugs to B-CMT cells, and the results showed that rapamycin and imatinib significantly inhibited the proliferation of the cells in vitro within a certain range of concentration, as well as induced G1 and G2 cell cycle arrest of B-CMT cells, respectively. In summary, the results of this report showed that B-CMT cell line might serve as a tool for future studies on tumor microenvironment and drug resistance.